Thermal and luminic comfort assessment in university classrooms in Tijuana, Baja California. Case of study FCITEC, Valle de las Palmas - María Teresa de la Cruz Chaidez; José Francisco Armendáriz López; Francisco José Martín del Campo Saray; Miguel Isaac Sahagún Valenzuela; María Cristina Castañón Bautista; Carmen García Gómez (Revista de Ciencias Tecnológicas, 2022)
About 2022, studies on environmental conditions inside classrooms have increased because they are related to well-being, performance, and student productivity in terms of concentration, attention, and learning during school hours. Assessing the conditions of the educational space once inhabited can be fundamental to identifying environmental adjustments that could improve achievement in learning through design strategies in school facilities in the locality. The evaluation of the thermal and luminic conditions of three classrooms designed to function with natural ventilation, in two buildings of the Universidad Autónoma of Baja California, in Tijuana, Mexico, during the cold-warm transition period is presented. Physical measurements of environmental indicators were made, including temperature, relative humidity, and daylight. A total of 181 students completed the environmental survey questionnaires. This study aimed to evaluate the interior environmental space conditions and determine the influence on occupants' comfort. Results showed that more than 50% of the students were in a thermal discomfort situation when the temperature was out of the range of 19.7°C -27.7° C, consistent with the application of the ASHRAE Adaptative Comfort Zones. Daylight values were below the minimum required of 300 Lux for educational classroom specificity in [1, 2] of the three classrooms. Building's orientations, West and South registered illuminance values that could produce glare and increase thermal discomfort due to high solar radiation. The results confirmed the close relationship between environmental conditions and students' comfort in classrooms.